Companies' strategies for competence development and personnel recruitment within employment increasing fields : paper presented at the European Conference on Educational Research (ECER) in Berlin, 13-16 September 2011 - Dietzen, Agnes [Verfasser]; Wünsche, Tom [Verfasser] (My University, 2011)
"The paper presents results from a study on competence-development activities along with the staff recruitment strategies of companies within employment increasing economic sectors. The empirical results will help to underpin the ongoing and intensifying academic discourse about the effectiveness and sustainability of vocational education and training (VET). This debate is prompted on the one hand by the higher competence requirements imposed by the expanding knowledge and service economy and, on the other hand, by a perception of graduates with Bachelor's degrees that also confer a professional qualification as potential new competitors for the same jobs as vocationally qualified skilled workers." (Textauszug, BIBB-Doku)
Keywords: G 1.2.3 Qualifikationsentwicklungen; G 1.2.3.2 Anforderungen & Bedarfe; G 2.3.4 Qualifikationswandel; S 5.3 Personalentwicklung; Qualifikationsforschung; Qualifikationsbedarf; Fachkräftebedarf; Personalpolitik; Betriebliche Berufsausbildung; Betriebliche Weiterbildung; Personalgewinnung